1984
DOI: 10.1177/070674378402900506
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Reliability of the Clinical Oral Examination in Psychiatry

Abstract: A study of the variability between raters in scoring an oral clinical examination in psychiatry in the format of the certification by the Royal College of Physicians and Surgeons of Canada is reported. A video-taped examination from another centre was rated independently by academic psychiatrists, nonacademic psychiatrists and residents. Considerable inter-rater differences between and within these groups were found. In particular, the averaging of the marks of pairs of raters as occurs in the actual certifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…8 It has also been demonstrated that the luck of the draw in selection of examiner and patient played a significant role in the outcome of postgraduate examinations in psychiatry using the traditional method. 6 Published findings of researchers on OSCE from its inception in 1975 to 2004 has reported it to be reliable, valid and objective with cost as its only major drawback. 9 The OSCE however, covers broader range like problem solving, communication skills, decision-making and patient management abilities.…”
Section: Advantages and Disadvantages Of Oscementioning
confidence: 97%
See 2 more Smart Citations
“…8 It has also been demonstrated that the luck of the draw in selection of examiner and patient played a significant role in the outcome of postgraduate examinations in psychiatry using the traditional method. 6 Published findings of researchers on OSCE from its inception in 1975 to 2004 has reported it to be reliable, valid and objective with cost as its only major drawback. 9 The OSCE however, covers broader range like problem solving, communication skills, decision-making and patient management abilities.…”
Section: Advantages and Disadvantages Of Oscementioning
confidence: 97%
“…It is comprised of several "stations" in which examinees are expected to perform a variety of clinical tasks within a specified time period against criteria formulated to the clinical skill, thus demonstrating competency of skills and/ or attitudes. The OSCE has been used to evaluate those areas most critical to performance of health care professionals, such as the ability to obtain/interpret data, problem-solve, teach, communicate, and handle unpredictable patient behavior, [3][4][5][6][7] which are otherwise impossible in the traditional clinical examination. Any attempt to evaluate these critical areas in the old-fashioned clinical case examination will seem to be assessing theory rather than simulating practical performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data gathered by the National Board of Medical Examinations in the USA (1960)(1961)(1962)(1963), involving over 10 000 medical students, showed that the correlation of independent evaluations by two examiners was less than 0.25 (Hubbard et al, 1963). It has also been demonstrated that the luck of the draw in selection of examiner and patient played a significant role in the outcome of postgraduate oral examinations in psychiatry (Leichner et al, 1984). Indeed, Leichner et al went on to suggest that the use of OSCEs may be a feasible means of improving the validity and reliability of oral examinations (Leichner et al, 1986).…”
Section: Simulated Patients and Clinical Examinationsmentioning
confidence: 99%
“…It has also been demonstrated that the luck of the draw in selection of examiner and patient played a significant role in the outcome of postgraduate oral examinations in psychiatry (Leichner et al, 1984). Indeed, Leichner et al went on to suggest that the use of OSCEs may be a feasible means of improving the validity and reliability of oral examinations (Leichner et al, 1986). …”
Section: Simulated Patients and Clinical Examinationsmentioning
confidence: 99%